Kualitas Teknologi Layanan Mandiri Aplikasi KAI Access (Studi Pada PT. Kereta Api Indonesia Persero Daop 9 Jember) - Yusita Titi Hapsari (Ekuitas: Jurnal Pendidikan Ekonomi, 2022)
After the Covid-19 pandemic, the service business moved more rapidly, this led to increased competition between service providers. One of them is transportation services. As a land transportation service provider, PT Kereta Api Indonesia (Persero) is an Indonesian state-owned company engaged in rail transportation services. One of the effects of the social distancing movement implemented by the government is that people are now more comfortable with independent services. The KAI Access application which has been developed and published since 2014 is one of the facilities of PT. KAI (Persero) which is able to fulfill digital-based services by providing independent access to prospective passengers and their passengers. Facilities obtained from the KAI Access application include ticket reservations, ticket schedule changes, ticket cancellations, KRL information, KAI Logistics, top up and billing, to taxi and bus ordering facilities. This study aims to describe the quality of self-service technology services provided by the KAI Access application owned by PT. KAI (Persero) at DAOP 9 Jember. This research uses descriptive qualitative research as its research method. The quality of self-service technology services from the KAI Access application at PT KAI (Persero) is the focus of this study. According to Parasuraman et al., service quality testing at PT. KAI (Persero) DAOP 9 Jember uses five dimensions of service quality, namely tangibles, reliability, responsiveness, assurance, and empathy. The results of the analysis of the service quality of the KAI Access application in this study concluded that the service quality of the KAI Access application at PT. KAI (Persero) can be said to be good. According to Parasuraman et al., there are five indicators of service quality, one of which is the Direct Evidence (Tangibles) indicator in the PT KAI access application service. (Persero) quite well. The people who use the KAI Access application service are used to using this technology. The Jember station continues to pay attention to officers who specifically assist the operation of the KAI Access application by providing customer service in train cars and at the station.